SUROBOYO BUS FARES SUFFICIENCY WITH WILLINGNESS TO PAY ASPECTS : CASE STUDY: PURABAYA BUS STATION – RAJAWALI SHELTER - Nugroho Utomo; Ibnu Sholichin; Praswidi Wiradiansyah (Journal of Civil Engineering Science and Technology (CI-TECH), 2020)
Suroboyo Bus is the one of public transportations based on Bus Rapid Transit as the implementations of Surabaya Municipality policy to fulfill needs of Surabaya citizens about proper public transportation according to security, safety and comfortable aspects. After it’s launching at April, 7th 2018, Suroboyo Bus has so many interests from Surabaya citizens who want to try for grand rides which it payments using plastic waste such as used drinking bottle or glass of mineral water. Payments method by using this plastic waste of drinking bottle in order to complying the objectives of Surabaya Municipality is reducing plastic wastes also citizens shouldn’t make a littering anywhere. This research is conducted to calculate how much Suroboyo Bus fares that sufficient with existing payments method due to Suroboyo Bus operations needs with using Willingness To Pay (WTP) analysis and Vehicle Operations Cost regulations.As the research results value of Willingness To Pay on weekday is IDR 4.784,12 and then on weekend is IDR 4.602,50. Value of Vehicle Operations Cost that Suroboyo Bus needed is IDR 13500 according with regulation standard from Directorate General of Land Transportations. Reviewed on load factor value 70% that appropriate with standards from Department of Transportations, so government must subsidize Vehicle Operations Cost for Suroboyo Bus with value IDR 300/passengers-km